AQUAGYM EXERCISES CONTRIBUTION AT THE HEALTH OF ADULTS - Aida Petrea (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Aqua Gym or aqua fitness is an element relatively new in our country that everyone, without restriction, can benefit, from children and young people up to age three. The novelty is given by the combination aerobic gymnastics - aquatic environment. The benefits of aerobic gymnastics combined with water effects on the body give a feeling of lightness and relaxation, with beneficial influence on cardiovascular and respiratory systems, strengthening joints and toning muscles, risk of injury being much lower, because the water reduces body weight by up to 85% depending on its depth and has a 12 times greater resistance than air. With aqua gym exercises, pounds can be taken off without drastic and exaggerated dieting, it gains posture, strengthens muscles, increases self-confidence, mind is more clear, gaining a benefical wellness for mind and body.